Antimicrobial and antimycotic photodynamic therapy (review of literature) - D. Yu. Semyonov; Yu. L. Vasil’ev; S. S. Dydykin; E. F. Stranadko; V. K. Shubin; Yu. K. Bogomazov; V. A. Morokhotov; A. N. Shcherbyuk; S. V. Morozov; Yu. I. Zakharov (Biomedical Photonics)
This review highlights the possibilities of photodynamic therapy (PDT) using drugs based on chlorin e6, aluminum phthalocyanine, methylene blue as photosensitizers for bacterial and fungal pathologies. This method was developed initially to treat tumor diseases, where it had shown its high efficiency and safety. Now photodynamic therapy is actively used in the treatment of cancers of the skin, bronchi, stomach, cervix, larynx, or other regions. However, numerous studies have been carried out for the entire existence of the method, demonstrating new possibilities of its application. This review highlights a number of studies in which the efficacy and safety of antimicrobial and antimycotic PDT were studied in vivo and in vitro. It has been proven to have a positive effect on the reparative processes in the wound. An experimental study was carried out to study the effectiveness of photodynamic therapy in the treatment of peritonitis in mice. Demonstrated anti-inflammatory potential in the treatment of autoimmune diseases.